Role of Quercetin in Diabetic Cardiomyopathy - Nor Hidayah Mustafa; Hawa Nordin Siti; Yusof Kamisah (Plants)
Diabetic cardiomyopathy is a significant and severe complication of diabetes that affects a large portion of the global population, with its prevalence continuing to rise. Secondary metabolites, including quercetin, have shown promising effects in mitigating the progression of diabetic cardiomyopathy by targeting multiple pathological mechanisms, including impaired insulin signaling, glucotoxicity, lipotoxicity, oxidative stress, inflammation, fibrosis, apoptosis, autophagy, mitochondrial dysfunction, cardiac stiffness, and disrupted calcium handling. Addressing these mechanisms is crucial to prevent left ventricular diastolic and systolic dysfunction in advanced stages of diabetic heart disease. Scientific evidence has highlighted the cardioprotective properties of quercetin at both the myocardial and cellular/molecular levels in diabetic models. Therefore, this review aims to present a comprehensive overview of the proposed mechanisms underlying quercetin’s beneficial effects, providing valuable insights that could inform future drug discovery efforts specific to diabetic cardiomyopathy.